2019
DOI: 10.1016/j.bbmt.2019.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes of Allogeneic Hematopoietic Cell Transplantation for Multiple Myeloma Using Three Different Conditioning Regimens

Abstract: Allogeneic hematopoietic cell transplantation (allo-HCT) is a potentially curative therapy for patients with multiple myeloma, as it provides a graft-versus-myeloma effect alongside a myeloma-free graft. Although reduced-intensity conditioning regimens decrease nonrelapse mortality (NRM), there is a paucity of data with regard to the ideal conditioning regimen in myeloma. We conducted a retrospective comparison of 3 different preparative regimens used for allo-HCT for multiple myeloma at our institution in rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Our observation of aGVHD incidence of 24%, the detrimental effect of aGVHD, and the beneficial effect of cGVHD on the outcome of the patients is in line with several previous studies [12,32,39]. For cGVHD, the rate of 62% in our study was in the upper range compared with 27-67% reported elsewhere [16,31,39,40]. This translated to the GRFS median of less than a year.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our observation of aGVHD incidence of 24%, the detrimental effect of aGVHD, and the beneficial effect of cGVHD on the outcome of the patients is in line with several previous studies [12,32,39]. For cGVHD, the rate of 62% in our study was in the upper range compared with 27-67% reported elsewhere [16,31,39,40]. This translated to the GRFS median of less than a year.…”
Section: Discussionsupporting
confidence: 91%
“…We were able to define cytogenetic risk according to current criteria [ 21 ] for less than half of the patients, approximately one-third of them with HR cytogenetics. Several studies have shown that allo-SCT could overcome the adverse prognosis of high cytogenetic risk [ 6 , 11 14 ], while others have not [ 15 , 16 ]. In our study, allo-SCT did not seem to benefit patients with HR cytogenetics despite a majority of them receiving allo-SCT in an upfront setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, long-term side effects of allo-SCT widely vary between individual patients and have to be seen as a dynamic process with changing burden of symptoms [ 47 ]. Thus, depending on the timepoint of symptom assessment, the rate of chronic GvHD of any grade ranges from 22% to 67% in different trials [ 17 , 24 , 37 , 44 , 48 , 49 ].…”
Section: Allogeneic Transplantation In Newly Diagnosed and Relapsed And/or Refractory Myelomamentioning
confidence: 99%
“…However, this intensive approach consistently was found to be associated with high rates of treatment‐related mortality (35%‐55%), which abrogated any benefits derived from improved disease control. Several recent small studies have evaluated less intensive, but still myeloablative, regimens and have demonstrated 3‐year OS rates of approximately 30% and 1‐year treatment‐related mortality rates of 19% to 37% . To the best of our knowledge, no contemporary systematic studies have evaluated more recent approaches to myeloablative conditioning.…”
Section: Introductionmentioning
confidence: 99%